UN Studio : design models, architecture, urbanism, infrastructure - Berkel, Ben van, 1957-; Bos, Caroline, 1959- (New York : Rizzoli, 2006)
"This is the complete monograph of UN Studio's output. The book begins with an essay that examines how architects can stop the proliferation of willful design by ceasing to design projects and instead develop design models that can be transferred from one project to another." "Divided by design model, the book's main section presents concepts and buildings in detail: from the initial, generative diagram through the digital-modeling process, to construction and final outcome."
Design models -- Inclusive principle -- Mathematical model -- Blob-to-box model -- V-model -- Deep-planning principle -- After image.
Includes bibliographical references (p. 392-395).
ARC
Keywords: UN Studio -- Catalogs; Architecture, Modern -- 20th century -- Catalogs; Architecture, Modern -- 21st century -- Catalogs; Architectural design -- Netherlands -- Amsterdam -- Catalogs